2016
DOI: 10.1016/j.ajhg.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic IARS Mutations Cause Growth Retardation with Prenatal Onset, Intellectual Disability, Muscular Hypotonia, and Infantile Hepatopathy

Abstract: tRNA synthetase deficiencies are a growing group of genetic diseases associated with tissue-specific, mostly neurological, phenotypes. In cattle, cytosolic isoleucyl-tRNA synthetase (IARS) missense mutations cause hereditary weak calf syndrome. Exome sequencing in three unrelated individuals with severe prenatal-onset growth retardation, intellectual disability, and muscular hypotonia revealed biallelic mutations in IARS. Studies in yeast confirmed the pathogenicity of identified mutations. Two of the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 36 publications
3
74
1
Order By: Relevance
“…Recently, Kopajtich et al reported three individuals harboring bi-allelic mutations in cytosolic isoleucyl-tRNA synthetase ( IARS ) (MIM: 600709). These individuals had a distinct syndrome of prenatal onset growth retardation, intellectual disability, and liver dysfunction [9]. Here, we report an additional subject with bi-allelic missense substitutions in IARS and overlapping clinical findings.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, Kopajtich et al reported three individuals harboring bi-allelic mutations in cytosolic isoleucyl-tRNA synthetase ( IARS ) (MIM: 600709). These individuals had a distinct syndrome of prenatal onset growth retardation, intellectual disability, and liver dysfunction [9]. Here, we report an additional subject with bi-allelic missense substitutions in IARS and overlapping clinical findings.…”
Section: Introductionmentioning
confidence: 89%
“…To evaluate the functional consequence of the IARS variants identified in the patient described here we performed yeast complementation assays utilizing a pYY1 expression construct. Similar studies have successfully revealed the functional consequences of many disease-associated aminoacyl-tRNA synthetase mutations (4) and were recently employed to study the functional consequences of other IARS variants (9). Here, the endogenous yeast gene is deleted and the ability of wild-type and mutant human IARS alleles to support yeast cell growth is used as a proxy for enzyme function.…”
Section: Yeast Complementation Assaysmentioning
confidence: 99%
“…Solid line indicates dominant mode of inheritance, dashed line indicates recessive mode of inheritance. References: AARS , DARS , HARS , IARS MARS , RARS , S ARS , W ARS , ARS , QARS , GARS , KARS , AARS 2 , CARS 2 , DARS 2 , EARS 2 , FARS 2 , HARS 2 , IARS 2 , LARS 2 , MARS 2 , NARS 2 , PARS 2 , RARS 2 , S ARS 2 , TARS 2 , VARS 2 , WARS 2 , YARS 2 .…”
Section: Mitochondrial Trna Synthetases (Ars2 Genes)mentioning
confidence: 99%
“…Yeast complementation assays have been used to demonstrate a loss-of-function effect on ARS function for mutations in eight genes implicated in recessive diseases ( AARS , AARS2 , HARS2 , IARS , KARS , LARS2 , MARS , VARS2 ) [6,44,47,48,52,57,63,64]. Similar to aminoacylation assays, in vivo studies in yeast have revealed a loss-of-function effect for GARS , YARS , AARS , and HARS mutations that cause dominant CMT disease (Table 2).…”
Section: Functional Studies To Predict the Pathogenicity Of Ars Variantsmentioning
confidence: 99%
“…For example, gene knock-down studies showed that reduced glutaminyl-( qars ) and isoleucyl-tRNA synthetase ( iars ) function in zebrafish cause, respectively: ( i ) reduced eye size and pigmentation, smaller brains, and lack of coordination; and ( ii ) growth retardation and brain deformity [47,54]. These data support a loss-of-function effect of QARS and IARS mutations in the associated autosomal recessive disease phenotypes (Table 1).…”
Section: Models To Study the Mechanism Of Ars Mutations In Human Diseasementioning
confidence: 99%